A strife of tongues : the Compromise of 1850 and the ideological foundations of the American Civil War - Maizlish, Stephen E., 1945- (Nation divided., 2018)
"A Strife of Tongues analyzes the debates over the Compromise of 1850 to reveal the underlying assumptions and values of the North and the South a decade before the outbreak of the Civil War. Rather than examining voting patterns, factional alignments, legislative maneuvering, and specific measures of the Compromise, this account looks at the language of the debate, the words of the senators and representatives, to discover the concepts and beliefs that defined the North and the South as the sectional confrontation approached. To a large extent, these opposing ideologies had common roots and were based on shared assumptions. Northerners and southerners had similar views of gender and masculinity, pursued the common goal of capital accumulation, and were in fundamental agreement over the superiority of the white race. But conflicting views of slavery, and especially slavery expansion, led to the development of highly divergent systems of belief about politics, economics, and society that would sustain the deepening sectional division and eventually support separation. This examination of the language of the debate yields a novel account of the dynamic driving the crisis of 1850 and sectional conflict generally. The ideological formulations of the Compromise debates of 1850 laid the foundations of the American Civil War"--